Comparison of livestock-associated and health care-associated MRSA: genes, virulence, and resistance - Mutters, Nico T.; Bieber, Christian Paul; Hauck, Catherine; Malek, Veronika; Frank, Uwe (Diagnostic microbiology and infectious disease, 2016)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) may colonize and infect humans with close contact to pigs. We compared phenotypic and genotypic differences in resistance and virulence of LA-MRSA isolates from farms and farmers with hospital-acquired methicillin-resistant S. aureus (HA-MRSA) and assessed carriage rates. Samples from pigs (n=330), occupationally exposed personnel (n=63), the farm environment (n=134), and hospital patients (n=220) were obtained. Approximately 50% (166/330) of pigs were MRSA positive. All LA-MRSA were resistant to tetracycline, compared to only 8% of HA-MRSA (P<0.001). In contrast, HA-MRSA isolates showed significantly higher resistance rates to quinolones (81% versus 7%; P<0.001). All strains isolated from occupationally exposed personnel (61.9%; 39/63) belonged to CC398. HA-MRSA isolates were diversely distributed, with predominance of CC5 (62.7%). Human strains carried significantly more virulence genes than porcine strains, especially exotoxins (P<0.001) and immune-evasion cluster genes (P<0.001). There were significant differences in resistance patterns and recognized genotypic virulence loci between LA-MRSA and HA-MRSA.